Creating salt refuges to protect amphibians from chytridiomycosis: first, do no harm - Relyea, Rick A.; Le Sage, Emily (Frontiers in Amphibian and Reptile Science, 2024)
In the fight against emerging pathogens, an important management strategy is to identify host refuges to prevent extinctions. Fungal pathogens (Batrachochytrium) are decimating amphibians around the world, but researchers have discovered that coastal amphibians living in high-salt water bodies can experience a refuge because the pathogens have lower survival outside the host in these conditions. This has led to the recommendation that managers should create disease refuges for amphibians by adding salt to water bodies. We review this literature and highlight that while some populations of coastal amphibians have evolved increased salt tolerance, most amphibian populations around the world have not. The relatively high concentrations of salt that are needed to kill the pathogens would cause widespread direct and indirect harm on amphibians and would kill most other aquatic taxa. Thus, intentionally salinizing freshwater habitats is a well-intentioned management strategy, but it is not a well-advised strategy.